The Influence of Workload and Motivation on the Performance of Employees of the Rakat Mufakat Village Bumdes in Tanah Bumbu Regency - U Usman; Irawanto; Rizalul Gadi; Jamili; Muhammad Mochtar Mandala Silam; Akhmad Riduan (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to analyze the effect of workload and motivation on employee performance at  BUMDes  of  the  people  of  Sebamban  Baru village, Tanah  bumbu  Regency.  This multiple linear regression equation is Y = a + b1 x1 + b2 x2 + e. The conclusion of this study is the regression equation Y = 17,870 + 399 x1 + 413x2 And the t test results show that workload and motivation have a significant effect on the performance of BUMDes Rakat Mufakat employees. Which is shown t count X1 = 911 < t table 2.052. It is proven that the null hypothesis (H0). Which states that workload variables affect employee performance at BUMDes Rakat Mufakat. While t count X2 = 2.402> 2.052 which states that motivation has a significant effect on employee performance. As for the f test, the calculation result of f count is 6,919 with a significance level of 0.04 which is smaller than 0.05, which means that simultaneously the effect between variable X and variable Y the amount of influence given by workload and motivation on the performance of BUMDes Rakat Mufakat employees is 33.9% and the remaining 66.1% is explained by other variables not examined in this study.